An Asian American Theology of Liberation - Wong, Tian An (Lever Press, 2023)
What does liberation mean for Asians at the core of an anti-Black, settler-colonial empire? This landmark book is the first to offer an Asian American theology of liberation for the present and future global crises. The broad scope of contemporary ideas that the book engages with will be of interest to students, activists, clergy, and scholars alike. Readers interested in radical politics, political theology, and Asian American history will find this book an important addition to their bookshelves. Providing an intersectional frame that considers the breadth and diversity of Asian American experiences alongside those of Black, Indigenous, and Latinx thinkers in the United States and across the globe, An Asian American Theology of Liberation puts Asian American theology in dialogue with theories from psychoanalysis, Afro-pessimism, Black Marxism, postcolonial studies, and queer theology. In this groundbreaking work, Wong Tian An combines archival research uncovering a much overlooked theology of liberation - born in the 1970s out of Asian Americans' struggles for political recognition and civil rights in the United States - with powerful analyses drawing from the theological, intellectual, and political developments of the last half century. This wide-ranging study connects urgent themes such as protest movements in Hong Kong, anti-Asian violence in the United States, and Indigenous struggles everywhere, while building on Asian theologies such as Dalit theology in India, theology of struggle in the Philippines, and Minjung theology in Korea. Drawing deeply and broadly across disciplines, the book altogether revives and renews an Asian American theology of liberation for a new generation.